2010
DOI: 10.1097/ico.0b013e3181bdf1cc
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence of Rabbit Corneas After Collagen Cross-Linking Treatment With Riboflavin and Ultraviolet A

Abstract: Purpose-To assess ultrastructural modifications in keratocytes and inflammatory cell response in rabbit corneas after riboflavin and ultraviolet A (UVA) exposure using immunoflurescence microscopy.Methods-Twenty adult New Zealand albino rabbits weighing 2.0 to 3.0 kg were used in this study. Two rabbits served as controls. The animals had their epithelia removed and were cross-linked with riboflavin 0.1% solution (10mgs riboflavin-5-phosphate in 10ml 20% dextran-T-500) applied every 3 minutes for 30 minutes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 15 publications
(20 reference statements)
2
30
0
Order By: Relevance
“…Both objective (14,15) and subjective (16) improvements were reported in eyes with keratoconus after CXL treatment, even in subjects under 18 (17). As collagen bonds are established at a depth of 250-350 µm in the anterior stroma, called the treatment zone (5,(18)(19)(20)(21), and for the protection of the endothelium, a minimum of 400 µm stromal thickness is suggested (5,22). However, according to other publications, a minimum of 330 µm of initial thickness is also sufficient for CXL after corneal swelling (23).…”
Section: Discussionmentioning
confidence: 99%
“…Both objective (14,15) and subjective (16) improvements were reported in eyes with keratoconus after CXL treatment, even in subjects under 18 (17). As collagen bonds are established at a depth of 250-350 µm in the anterior stroma, called the treatment zone (5,(18)(19)(20)(21), and for the protection of the endothelium, a minimum of 400 µm stromal thickness is suggested (5,22). However, according to other publications, a minimum of 330 µm of initial thickness is also sufficient for CXL after corneal swelling (23).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence microscopy was proposed by Bottós et al (20) in 2008 as new approach to indirectly visualize the effect of collagen cross-linking, which was later validated by other authors (30) . Bottós et al (20) addressed the isolated effect of riboflavin on the collagen organization and corneal dehydration by applying 0,1% riboflavin solution to de-epithelialized corneas without UVA exposure.…”
Section: A B C D E Fmentioning
confidence: 99%
“…Hence, the present study was carried out, and it demonstrated an almost twofold reduction in vaginal cell viability after UVA irradiation caused by increased necrosis. Indeed, increased apoptosis and necrosis after photopolymerization in other cell types such as keratocytes have been reported [27]. The deleterious effects of the long-wave UVA irradiation were due to lipid peroxidation and oxidative stress resulting from free radicals released by the endogenous target molecules.…”
Section: Discussionmentioning
confidence: 99%